Zoledronic acid affects the process of Porphyromonas gingivalis infecting oral mucosal epithelial barrier: An in-vivo and in-vitro study - Sun, Hanyu; Li, Pugeng; Kong, Qingci; Deng, Feilong; Yu, Xiaolin (Frontiers in Cellular and Infection Microbiology, 2023)
Zoledronic acid (ZA), one of the commonly used bisphosphonates, is mainly used for bone-metabolic diseases. Studies proved that ZA has adverse effects on oral soft tissues. As the first line of innate immunity, the gingival epithelium could be infected by periodontal pathogens, which is a key process of the initiation of periodontal diseases. Yet, how ZA affects the periodontal pathogens infecting the epithelial barrier remains unclear. This study aimed to investigate the influences of ZA on the process of Porphyromonas gingivalis (P. gingivalis) infecting the gingival epithelial barrier via in-vitro and in-vivo experiments. In the in-vitro experiments, under the condition of different concentrations of ZA (0, 1, 10, and 100 μM), P. gingivalis was used to infect human gingival epithelial cells (HGECs). The infections were detected by transmission electron microscope and confocal laser scanning microscope. Besides, the internalization assay was applied to quantify the P. gingivalis, which infected the HGECs, in the different groups. To evaluate the expression levels of pro-inflammatory cytokines, including interleukin (IL)-1β, IL-6, and IL-8, by infected HGECs, real-time quantitative reverse transcription-polymerase chain reactions were applied. In the in-vivo experiments, rats were given ZA solution (ZA group) or saline (control group) by tail intravenous injection for 8 weeks. Subsequently, we put ligatures around the maxillary second molars of all the rats and inoculated P. gingivalis to the gingiva every other day from day 1 to day 13. The rats were sacrificed on days 3, 7, and 14 for micro-CT and histological analyses. The in-vitro results manifested that the quantity of P. gingivalis that had infected HGECs increased with the ZA concentrations. Pro-inflammatory cytokines expression by HGECs were significantly increased by 100 μM ZA. In the in-vivo study, compared to the control group, more P. gingivalis was detected in the superficial layer of gingival epithelium in the ZA group. Besides, ZA significantly increased the expression level of IL-1β on day 14 and IL-6 on days 7 and 14 in gingival tissues. These findings suggest that the oral epithelial tissues of patients who receive high-dose ZA treatment may be more susceptible to periodontal infections, resulting in severe inflammatory conditions.